2023
DOI: 10.3390/children10030425
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Self-Esteem in Children with Specific Learning Disorders after Donkey-Assisted Therapy

Abstract: Dyslexia is a learning disorder related to receptive language characterized by difficulties with decoding, fluent word recognition, automatic naming skills and/or reading comprehension skills. It usually leads to severe functional impairment and the permanent need for support and interventions. Since animal-assisted interventions (AAIs) have been found to improve physical, emotional, cognitive and/or social functioning in humans, the aim of this study is to demonstrate the effectiveness of onotherapy on childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Preceding research has indicated negative school results due to mental illness (Burnett-Zeigler et al, 2012 ) with adverse long-term effects on academic outcomes (Bailey et al, 2018 ; Wagner et al, 2015 ). EAS has previously been shown to facilitate empowerment processes and enhance self-confidence, self-esteem, and ability to handle responsibility (Xie, 2013 ) and reduce problematic behaviours such as aggressiveness and assertiveness (Bachi et al, 2012 ; Corallo et al, 2023 ; Lee et al, 2016 ; Wilson et al, 2017 ). EAS can help children and adolescents overcome the adverse effects of mental illness and thus facilitate participation in activities to support their experience of being a capable person (García-Carrión et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preceding research has indicated negative school results due to mental illness (Burnett-Zeigler et al, 2012 ) with adverse long-term effects on academic outcomes (Bailey et al, 2018 ; Wagner et al, 2015 ). EAS has previously been shown to facilitate empowerment processes and enhance self-confidence, self-esteem, and ability to handle responsibility (Xie, 2013 ) and reduce problematic behaviours such as aggressiveness and assertiveness (Bachi et al, 2012 ; Corallo et al, 2023 ; Lee et al, 2016 ; Wilson et al, 2017 ). EAS can help children and adolescents overcome the adverse effects of mental illness and thus facilitate participation in activities to support their experience of being a capable person (García-Carrión et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…EAS for children and adolescents with mental ill health, including symptoms such as anxiety and depression, has resulted in improved self-esteem, self-confidence, assertiveness, life satisfaction, and self-control, as well as a reduction of problematic behaviours such as aggressiveness and assertiveness (Bachi et al, 2012 ; Corallo et al, 2023 ; Lee et al, 2016 ; Wilson et al, 2017 ). A recent interview study among children and adolescents with mental health conditions showed that the participating children and adolescents during and after they had received EAS experienced innate calmness, improved self-esteem, and self-confidence (Punzo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This makes gaining insight into any effectiveness problematic. Despite this, there are indications that children benefit from programs involving animals [ 11 , 12 , 13 , 33 , 35 ]: for example, AAIs for dyslexia could increase self-esteem and improve cognitive functions and language skills recovery [ 36 ].…”
Section: Introduction and Hypothesesmentioning
confidence: 99%